Long term observations on sheep experimentally infected with Brucella Melitensis - ΠΑΠΑΔΟΠΟΥΛΟΣ, Ο.; ΣΑΡΡΗΣ, Κ.; ΠΑΠΑΝΑΣΤΑΣΟΠΟΥΛΟΣ, Μ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Six pregnant ewes were subcutaneously injected with 5 x10s live Brucella melitensis biotype 1 organisms. Observations on their serological response during the first six months post infection have been published earlier (Madad, 1979). In this paper, the observations during the following 24 month period, up to the 30th month, are reported. Four ewes that survived to the end of the experiment were still positive in the serum agglutination (titres 160, 212, 106 and 40 i.u./ml), complement fixation (titres 288, 384, 288 and 36 EEC u./ml) and Rose Bengal Plate tests. Two female lambs, born a few weeks post infection, remained negative during the present period of observation. Two rams, that were housed with the group from the 6th to the 30th month, remained negative. Three lambs, born on the 18th, 27th and 29th months had antibodies, that were considered to be of maternal origin. At the end of the experiment, brucellae were not detected by culture or guinea pig inoculation of material from the udder, uterus, retropharyngeal, internal iliac and supramammary lymph nodes of any of the surviving animals.